Pengaruh Nada Suara Pencerita Storytelling dan Gambar Bergerak Pada Media Digital Youtube pada Peningkatan Kemampuan Mengingat Berurutan Peserta Program Sekolahku YKAKI Jakarta - Retno Palupi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The concept of learning with video aids through the Youtube application is an option in the learning model of the Sekolahku YKAKI (Indonesian Care for Cancer Kids Foundation) program to facilitate memory strengthening by using repeated videos. This research is a qualitative research related to problems with the procedures for collecting data from interviews, observations, and archives. The activity of children watching videos is scheduled to be repeated with the assistance of the teacher, it is hoped that it will provide benefits for improving the memory of both the whole series of stories, as well as some of the details contained in the recordings. This activity is beneficial in the Sekolaku/My School program of YKAKI. Children who participate in Sekolahku/My School program are children with cancer who are undergoing treatment with various methods that consume energy and interfere with learning concentration. Inserting a message through a story using Youtube media which is specially made with the voice of the chosen narrator and equipped with sound effects supporting the story makes this YouTube video an option for memory strengthening in the learning model because there is a dynamic emphasis on the narrator's intonation with structured repetition.